The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1161/circulationaha.113.002424
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in Cardiovascular Disease and Its Risk Factors in Japanese

Abstract: Background— Changes in lifestyle and advances in medical technology during the past half century are likely to have affected the incidence and mortality of cardiovascular disease and the prevalence of its risk factors in Japan. Methods and Results— We established 5 cohorts consisting of residents aged ≥40 years in a Japanese community, in 1961 (n=1618), 1974 (n=2038), 1983 (n=2459), 1993 (n=1983), and 2002 (n=3108), and followed up each cohort for 7 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
207
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 255 publications
(226 citation statements)
references
References 32 publications
9
207
2
1
Order By: Relevance
“…The national value of the prevalence of hyperlipidemia using the same definition as in this study has not been reported. However, the observed prevalence of hyperlipidemia was similar to that reported in the other areas of Japan [40][41][42][43] . The clinical characteristics of subjects at baseline according to the status for hyperlipidemia are shown in Table 2.…”
Section: Methodssupporting
confidence: 88%
“…The national value of the prevalence of hyperlipidemia using the same definition as in this study has not been reported. However, the observed prevalence of hyperlipidemia was similar to that reported in the other areas of Japan [40][41][42][43] . The clinical characteristics of subjects at baseline according to the status for hyperlipidemia are shown in Table 2.…”
Section: Methodssupporting
confidence: 88%
“…The population of the town in 2016 was ≈8500. Full community surveys of the residents have been repeated since 1961 10. Comprehensive surveys of cognitive impairment in the elderly of this town have been conducted since 1985 11.…”
Section: Methodsmentioning
confidence: 99%
“…The Hisayama Study is a population‐based cohort study conducted to explore the risk factors for cardiovascular disease and dementia in a general Japanese population 10, 11. The most important feature of the study is that the dementia subtypes were diagnosed by detailed neurologic and morphologic examination, including neuroimaging and autopsy.…”
Section: Introductionmentioning
confidence: 99%
“…This finding may be influenced by the fact that the incidence of morbidity or mortality of CAD is lower in the Japanese than in Western populations. In the Hisayama studies, the incidence and mortality of CAD in Japanese patients were reported to be approximately 30% 29,30) . Taken together, these results suggest that longitudinal studies are needed to evaluate the association between the CAC score and rate of long-term coronary events in both asymptomatic and symptomatic Japanese individuals.…”
Section: Cac Score and Cardiovascular Morbidity And Mortality In The mentioning
confidence: 99%